2023
DOI: 10.3389/fonc.2023.1133491
|View full text |Cite
|
Sign up to set email alerts
|

AI diagnostic performance based on multiple imaging modalities for ovarian tumor: A systematic review and meta-analysis

Abstract: BackgroundIn recent years, AI has been applied to disease diagnosis in many medical and engineering researches. We aimed to explore the diagnostic performance of the models based on different imaging modalities for ovarian cancer.MethodsPubMed, EMBASE, Web of Science, and Wanfang Database were searched. The search scope was all published Chinese and English literatures about AI diagnosis of benign and malignant ovarian tumors. The literature was screened and data extracted according to inclusion and exclusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Certainly, there are other recent meta-analyses addressing the performance of artificial intelligence approaches to the differential diagnosis of adnexal masses [24,70,71]. However, our results cannot be compared with these meta-analyses.…”
Section: Strengths and Limitationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Certainly, there are other recent meta-analyses addressing the performance of artificial intelligence approaches to the differential diagnosis of adnexal masses [24,70,71]. However, our results cannot be compared with these meta-analyses.…”
Section: Strengths and Limitationsmentioning
confidence: 80%
“…Finally, Ma et al reported a meta-analysis including 11 studies, three of them using ultrasound-based approaches [71]. Two of them used DL, but did not compare this to expert examination and it was not included in our meta-analysis [36].…”
Section: Strengths and Limitationsmentioning
confidence: 99%